Correlates of Post-Stroke Brain Plasticity, Relationship to Pathophysiological Settings and Implications for Human Proof-of-Concept Studies - Sanchez-Mendoza, Eduardo H.; Hermann, Dirk Matthias (Frontiers in Cellular Neuroscience, 2016)
The promotion of neurological recovery by enhancing neuroplasticity has recently obtained strong attention in the stroke field. Experimental studies support the hypothesis that stroke recovery can be improved by therapeutic interventions that augment neuronal sprouting. However plasticity responses of neurons are highly complex, involving the growth and differentiation of axons, dendrites, dendritic spines and synapses, which depend on the pathophysiological setting and are tightly controlled by extracellular and intracellular signals. Thorough mechanistic insights are needed into how neuronal plasticity is influenced by plasticity-promoting therapies in order not to risk the success of future clinical proof-of-concept studies. Key words: Clinical translation, neuronal differentiation, neuronal plasticity, neuronal regeneration, restorative therapy.